IMPLEMENTASI KEBIJAKAN PEMBANGUNAN KEPARIWISATAAN BUKIT TANGKEBAN KABUPATEN PEMALANG - Shafa Tasya Kamila; Endang Larasati; Tri Yuniningsih (Journal of Public Policy and Management Review, 2023)
The Pemalang Regency Government issued Pemalang Regency Regional Regulation Number 19 of 2016 concerning the Pemalang Regency Tourism Development Master Plan for 2017-2025. This regional regulation is a policy that serves as a guideline in carrying out tourism development and development on Tangkeban Hill, but the implementation of this policy is not yet optimal. This research aims to analyze the implementation of tourism development policies on Tangkeban Hill and identify supporting and inhibiting factors. The method used is descriptive qualitative with data collection through observation, interviews and documentation. The results of the research show that in general the construction and development of Tangkeban Hill is in accordance with the contents of the policy even though there are aspects that are not yet optimal, namely aspects of target accuracy and environmental accuracy. Supporting factors consist of communication flexibility, a positive degree of disposition and an appropriate bureaucratic structure, while factors inhibiting implementation are resources. Recommendations that can be given are more intensive and massive tourism human resource training, direct and regular socialization regarding tourism development policies (Ripparkab) and Sapta Pesona, and the need to reconstruct tourism revenue sharing, so that the budget posture for operational needs is more sufficient to improve quality. and quantity of tourist destinations.